The Pine Branch, March 1927 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1927)
The Pine Branch, March 1927. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1927. Includes: editorials, photographs, poems, short stories, and other writings. Dedicated to Elizabeth Henslee of the Class of 1926.
Writers Inferno - Christine Meadows 5 | Mist - Lucile Nix 12 | On The Tip Of His Tongue - Lorene Tittle 13 | Nature Holds Sway - Christine Meadows: 19 | The Parisian Doll - E McRee 20 | A Southern Moon - M L Moran 28 | Editorial 29 | Y W C A Notes 31 | Society Notes 32 | Athletic Notes 34 | Locals 35 | Alumnae Notes 36 | Notes 39
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education